Implementasi Kurikulum Merdeka Pada Mata Pelajaran PAI Dalam Menunjang Pembentukan Karakter Religius Peserta Didik - Saepul Rohim; Icha Silvia Matien (MASAGI : Jurnal Pendidikan Agama Islam, 2026)
This study aims to describe the implementation of the Independent Curriculum in Islamic Religious Education subjects in supporting the formation of religious character in phase E students at SMA Ciledug Garut. Character issues among students are the main background of this study, considering the importance of religious values in supporting a faithful and noble personality. This study uses a descriptive method with a qualitative approach. The data sources in this study consist of primary data obtained from interviews and observations, as well as secondary data in the form of relevant documents and literature. The results of the study indicate that the implementation of the Independent Curriculum in Islamic Religious Education learning is quite effective in supporting the formation of religious character in students. Islamic Religious Education teachers are able to integrate religious values into learning and school activities. Students show improvements in terms of religious discipline, honesty, and concern for others. However, there are still obstacles such as the lack of active participation in some lessons. The Independent Curriculum provides flexible space for teachers and schools to foster religious character contextually.Keywords: Independent Curriculum, Islamic Religious Education, Religious Character of Phase E Students